Exploring the Architecture of Place in America's Farmers Markets - Albright, Kathryn (University of Cincinnati Press, 2020)
Exploring the Architecture of Place in America's Farmers Markets explores the elusive architectural states of these beloved community-gathering places. From classic market buildings such as Findlay Market in Cincinnati, to open-air pavilions in Durham North Carolina and pop-up canopy markets in Staunton, Virginia, the country currently has over 8,700 seasonal and year-round farmers markets. Architect, teacher, and founder of the Friends of the Farmers Market, Katheryn Clarke Albright combines historically informed architectural observation with interview material and images drawn from conversations with farmers, vendors, market managers and shoppers. Using eight scales of interaction and interface, Albright presents in-depth case studies to demonstrate how architectural elements and spatial conditions foster social and economic exchange between vendors, shoppers, and the community at large. Albright looks ahead to an emerging typology-the mobile market-bringing local farmers and healthy foods to underserved neighborhoods. The impact farmers markets make on their local communities inspires place-making, improves the local economy, and preserves rural livelihoods. Developed organically and distinctively out of the space they occupy, these markets create and revitalize communities as rich as the produce they sell.